PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA CANCHA DE FUTBOL-SALA, CON CUBIERTA Y CESPED SINTÉTICO, EN LA CIUDAD DE PALANDA (SECTOR EL SUI), PROVINCIA DE ZAMORA CHINCHIPE - Ávila Torres, Darwin Saúl (2015)
This project aims to present a proposal for the implementation of a company dedicated to rent a Soccer-Room with deck and Turf City Palanda, the same as it faces economic social and business development. The aim of this study is to determine the feasibility of implementing a court Synthetic, based on the study of market, Technical, Economic and Financial and Financial Evaluation. The methodology is based on the achievement of project objectives, the use of methods and techniques allowed us to gather accurate information in order to determine our potential claimants will. In the market study analyzed: The Potential, Real, Effective, supply and unsatisfied demand, demand for this statistical sampling, which was the economically active population in 2014 with a total 1.245 people for a total of 294 surveys were used. Technical Study on the size and location of the company is determined, the same to be located in the City of Palanda via Zumba, a place that provides the conditions and all the basic facilities for execution. Installed capacity lend the company is 24 hours a day, giving a total of 8.760 hours, which represents 100%; while the spare capacity is estimated prudent start during the first five years with 30% of installed capacity, and from the sixth year is to work with a capacity of 36%. 5 In the legal and organizational study some legal aspects required for normal operation is determined as: its mission, vision, type of business, its hierarchy and functions manuals. Within the Financial Study an initial investment of $ 71.579,47 dollars was established, which will be funded by the National Development Bank whose amount is $ 31.579,47 dollars equivalent to 44% of the investment, with an effective interest rate 15% annual; while 56% will be financed by the partners in the amount of $ 40.000,00. The financial evaluation presents the following results: Net Present Value (NPV) is $ 33.433,4 dollars; The Internal Rate of Return (IRR) is 24,00%; Sensitivity Analysis in an increase in the cost of the project is 14,00% insensitive, yielding a score of 0,99 and a decrease in revenue of 12,33% the project is not sensitive and results 0,99; Benefit Cost Ratio is $ 1.36 for every dollar invested profits of 36 ctvs receives., And it should be noted that the investment will pay off in 7 years 10 months and 6 days. And finally, based on all the studies it arises their respective conclusions and recommendations.